Pengaruh Model Pembelajarn Kooperatif Type Think Pair Share dalam Pelajaran Bahasa Indonesia terhadap Kemampuan Membaca Pemahaman Siswa Kelas VI SDI Manumuti - Flaviani Resiansi Koy Mali (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of the Think Pair Share (TPS) type cooperative learning model on the reading comprehension ability of grade VI students of SDI Manumuti. The study uses a quantitative approach with a Pre-Experimental One Group Pretest–Posttest Design. The research sample amounted to 23 students in grade VI of SDI Manumuti who were selected using the purposive sampling technique. The research instrument was in the form of reading comprehension tests provided before and after the application of the Think Pair Share learning model. Data analysis was carried out using descriptive statistics and inferential statistics through the paired sample t-test. The results showed that the average pretest score was 59.56, while the average posttest score increased to 83.04 with a mean gain of 23.48. These results show that the application of the Think Pair Share learning model is able to significantly improve students' reading comprehension skills. The stages of independent thinking, discussing in pairs, and sharing the results of the discussion (share) provide opportunities for students to actively build understanding, improve critical thinking skills, and strengthen the ability to find main ideas, important information, and conclude the content of the reading. Thus, the Think Pair Share type cooperative learning model can be used as an alternative to the Indonesian language learning model to improve the reading comprehension ability of elementary school students.